The Role of Boyolali District Bawaslu in Supervising Village Heads' Neutrality on Social Media in The 2024 Regional Head Elections - Rakhul Akbar Maulana; Labib Muttaqin (Universitas Muhammadiyah Surakarta, 2025)
Regional Head Election (Pilkada) is one of the important instruments in the democratic system in Indonesia. However, in its implementation, the neutrality of village heads often becomes a problem that can affect the integrity of Pilkada, especially through the use of social media. This study aims to analyze: 1) The role of the Election Supervisory Agency (Bawaslu) in maintaining the neutrality of village heads during the Pilkada, and 2) The role of Bawaslu Boyolali Regency in overseeing the neutrality of village heads on social media. The research method used is empirical juridical which examines legal provisions and conducts interviews with members of Bawaslu Boyolali Regency. The results showed that Bawaslu has a strategic role in overseeing the neutrality of village heads through socialization, direct supervision, as well as coordination with local governments and giving sanctions to violating village heads. However, this supervision faces obstacles in the form of limited resources and low awareness of village heads regarding neutrality rules, and in overseeing the neutrality of village heads on social media, Bawaslu Boyolali Regency implements a digital monitoring strategy, early detection of violations, coordination with related parties, socialization to village heads, and counseling to the public to monitor and report violations. Based on the research results, strengthening regulations and monitoring technology, increasing political literacy for village heads, and synergy between the government, Bawaslu, and the community are needed to ensure fair, transparent, and democratic elections.